Level of Integration in Modular System Curriculum in Medical Colleges of KPK, Pakistan: Integration in Modular System Curriculum - Ahmed, Fawad; Aman, Qari Muhammad Younas; Nawaz, Jawairia; Zaman, Laiba; Asghar, Faiqa; Hamza, Muhammad; Rani, Ramla; Sajid, Osama; Ismail, Aiza; Iqbal, Faiqa (Pakistan Journal of Health Sciences, 2025)
Integrated medical education links basic sciences with clinical exposure, enhancing critical thinking. The World Federation of Medical Education (WFME) standards now require integrated teaching for graduates seeking US residency. KPK implemented Harden’s Ladder integration in 2018, but the extent of its integration is unknown. Objective: To assess the integration level using Harden’s Ladder of Integration of medical colleges in KPK and examine variations across institutions, faculty profiles, and demographic data. Methods: A cross-sectional study was conducted from October 2024 to February 2025 across 13 public and private medical colleges within KPK. Faculty members received a validated questionnaire based on Harden’s Ladder, which was distributed through convenience sampling. The study employed Chi-square and Fisher’s exact tests to investigate the relationship between faculty demographics and levels of integration. Results: 99 faculty members participated. All faculty members reported full implementation of Step 5, which represents temporal coordination, whereas Steps 7-11 showed implementation in ≤50% of colleges (7 colleges). Senior faculty members with >3 years of experience observed better integration levels. The statistical analysis revealed significant institutional differences (p < 0.05) that were evenly distributed across colleges. Conclusions: Temporal coordination (Step 5) is fully implemented, but advanced integration is inconsistent. Faculty/institutional factors significantly influence outcomes, potentially compromising WFME accreditation requirements for US residency eligibility. Targeted interventions are recommended to bridge this gap.